THE LIVING QURAN STUDY (Analysing the Participation of University Students’ Parents in Learning during The Covid -19 Pandemic) - Hamka Hasan (Qur'an and Hadith Academic Society, 2022)
Online learning in the Covid-19 pandemic era was a new experience for lecturers, teachers,educators, and parents. Online learning in kindergarten, elementary school, junior highschooll, and senior high school levelss relied on the parents’ involvement and guidance itoptimal. This article responded to the absence of a study about the role of universitystudents’ parents in online learning in covid 19 pandemic. This study aimed to explain therole of parents of university students in online learning during covid 19 pandemic, whichwas conducted from home. It is qualitative research with a survey method involving 34students of the Faculty of Dirasat Islamiyah, State Islamic University of Syarif HidayatullahJakarta, on September 2021 on the subject of Al-Quran Memorization. The Faculty usedArabic language specializing it from other faculties. A questionnaire using g-form was usedas the data collection instrument considering that the study was carried out when theacademic activities were arranged in covid 19 pandemic era. The data we obtained werethematically grouped based on the research questions. They were then analyzed throughthree stages: data restatement, description, and interpretation. The study found that manyparents were involved in online learning during the Covid -19 pandemic. Their roles areclassified into academic, material, and motivational. The study was limited to one Faculty ina university and only investigated the parents’ role in guiding their children in onlinelearning of Alquran memorization subject. Further study should be carried out in a widerscale with more various variables.